From migration to urban sprawl in Flanders (Belgium). - Loris, Isabelle; Pisman, Ann (My University, 2017)
Der Beitrag untersucht vor dem Hintergund von Bevölkerungsprognosen den Einfluß von externer Zuwanderung und Binnenwanderung auf die Zersiedelung der Städte und Stadtregionen in Belgien, beleuchtet die Wanderungsmotive und fragt nach den Möglichkeiten von Raumplanung und Politik, diese Entwicklungen zu steuern.

Belgium, and especially Flanders, is recently developping new policy plans for the future spatial development. Within this context a discussion is going on about the strategies to deal with the ungoing urban sprawl. In this paper we will first focus on migration figures, and draw up a map with current migration patterns in Belgium. This map faces the residential pressure level of the municipalities and the regional housing market areas. This housing pressure is the result of depositing the growth in households relative to the available building possibilities. Secondly we will analyse the forecasted population growth in Flanders. Immigration to Belgium comes mainly from the rest of Europe, primarily from the group of 20-50 year olds. From 2040 on growth will only be due to external immigration. This external immigration arrives on the one hand basically in the larger cities. The internal migration, on the other hand, shows a pattern away from these larger cities. Especially the cities outlying edges and the rural areas have a growth at the expense of city centers. Accordingly the current population is changing. Within Belgium and Flanders, as in most other Western European countries, we are confronted with the ageing of the population and with a limited growth of the number of households mainly because of smaller households. Finally we confront the migration patterns, the population forecasts and the disponsibility of building plots. The large surplus of building opportunities, especially in rural areas, drives along the suburbanization. This urban sprawl in turn leads to the known dispersed settlement pattern in Flanders, the northern part of Belgium. In this context and in relation to European trends, we examine how the government can steer upon spatial planning and in particular on the available building possibilities.
Keywords: Bevölkerungsentwicklung; Einwanderung; Zuwanderung; Binnenwanderung; Wohnungsbedarf; Stadtumland; Suburbanisierung; Zersiedelung; Raumplanungspolitik